ASPEK HUMANISME POLIGAMI (Analisis Feminimisme terhadap Pemikiran Muhammad Shahrur Mengenai Syarat-syarat Poligami) - Basyar, Khoirul (RELIGIA, 2009)
According to Shahrur, Allah does not only allow polygamy, but also recommends polygamy if someone fulfills two conditions: first, the second, third, and fourth wife are widows who have fatherless child; second, the existence of worry not to do justice to the fatherless child without marrying his/her mother. Order to do polygamy will be invalid if the two conditions do not exist. Shahrur often use Qur’an more than Prophet Sunnah, and does not use ijma’ and qiyas. Interpreting of the two term is different from the previous scholars in general.